Status Resistensi Nyamuk Aedes Albopictus Terhadap Insektisida Sipermetrin Di Pelabuhan Meral Kabupaten Karimun Provinsi Kepulauan Riau Tahun 2022 - Risman Kurnia; Mutia Dian Safitri; Armen Zufri; Rizki Maisar Putra (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
The use of cypermethrin insecticide is one of the strategies in vector control that has been carried out by the Port Health Office of Karimun Regency. It is necessary to evaluate the use of insecticides because of the threat of resistance in controlling dengue hemorrhagic fever. The purpose of this study was to determine the resistance of Aedes albopictus mosquitoes to cypermethrin insecticides in the Meral Port area at the Port Health Office of Karimun Regency. This type of research was a quasi-experimental with a posttest only control group design. The population of this study was Aedes albopictus mosquitoes in the Meral Port area while the samples taken were 100 Aedes albopictus mosquitoes. The results showed that the resistance status of the Aedes albopictus mosquito to cypermethrin in the Meral Harbor area was in the vulnerable category with a mortality percentage of >98%. The Port Health Office of Karimun Regency is expected to be able to evaluate and follow up regularly on vector control activities that have been carried out in the Meral Port area and the need to periodically test mosquito susceptibility to insecticides with different methods. It is necessary to rotate the use of insecticides for mosquito control and re-do mosquito nest eradication (PSN) in the Meral Port area.